PM2.5 induces mitochondrial dysfunction via AHR-mediated cyp1a1 overexpression during zebrafish heart development. (15th March 2023) - Chen, Jin; Zhang, Mingxuan; Zou, Hongmei; Aniagu, Stanley; Jiang, Yan; Chen, Tao
Abstract: Accumulating evidence suggests an association between maternal PM2.5 exposure and congenital heart diseases, but the underlying mechanisms remain unclear. We previously reported that PM2.5 induces cardiac malformations in zebrafish embryos via the aryl hydrocarbon receptor (AHR) pathway, which mediates the generation of reactive oxygen species (ROS). Since mitochondria are not only the main source of ROS but also sensitive to oxidative damage, we hypothesize that mitochondria may play an important role in the cardiac developmental toxicity of PM2.5. In this study, we demonstrated that extractable organic matter (EOM) from PM2.5 caused mitochondrial dysfunction in the heart of zebrafish embryos, including increased mitochondrial ROS (mtROS) levels, mitochondrial permeability transition pore (mPTP) opening, mitochondrial membrane potential (MMP) collapse, reduced mitochondrial ATP levels, and decreased expression levels of the mRNAs encoding mitochondrial proteins, which were attenuated by either pharmacological or genetic inhibition of AHR. We further demonstrated that improving mitochondrial function by inhibiting mPTP opening with Cyclosporin A suppressed the EOM-induced intracellular ROS and mtROS generation, MMP collapse, intrinsic apoptosis, and heart defects. Moreover, the EOM-induced mPTP opening was counteracted by inhibiting mtROS with mitoquinone mesylate (MitoQ). Supplementation with MitoQ also attenuated the EOM-induced mitochondrial dysfunction, apoptosis and heart defects. Additionally, knockdown of cyp1a1 but not cyp1b1 attenuated the EOM-induced mtROS generation and heart defects. Taken together, this study indicates that PM2.5 triggers mtROS generation via AHR-mediated cyp1a1 overexpression, which then causes mPTP opening and mitochondrial dysfunction, leading to apoptosis and heart defects. Graphical Abstract: ga1 Highlights: PM2.5 induces mitochondrial dysfunction in the heart of zebrafish embryos. Inhibition of mPTP opening attenuates PM2.5-induced apoptosis and heart defects. Inhibition of mtROS alleviates PM2.5-induced mitochondrial dysfunction. Cyp1a1 but not cyp1b1 overexpression contributes to PM2.5-induce mtROS generation.